Optimasi Pemanfaatan Air Waduk Sistem Semi Kaskade Waduk Pacal dan Waduk Gongseng dengan Menggunakan Program Linear - Agustina, Nia; Rahman, Rizki Robbi; Indriyani, Dwi (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2024)
Pacal Reservoir and Gongseng Reservoir are reservoirs located in Temayang District, Bojonegoro Regency, East Java. These two reservoirs irrigate the Pacal Irrigation Area with an area of 7.049 Ha with other functions of the Gongseng Reservoir as a raw water provider, potentially as a power plant, and able to reduce flooding. This study aims to determine the optimization of water utilization of Pacal Reservoir and Gongseng Reservoir to meet the needs of irrigation water and raw water in the next 10 years. Optimization is carried out using a linear program with Microsoft Excel Solver Add-ins to get the optimal reservoir water utilization to meet the needs by maximizing the profit of agricultural products in irrigation. From the results of the analysis of reservoir water utilization that has been carried out for the next 10 years, it is found that the amount of irrigation water needed for the existing cropping pattern is 2,89 m3/det, for alternative cropping pattern 2 is 3,94 m3/det, and for alternative 3 is 2,51 m3/det. The raw water demand for Temayang, Sukosewu, Sugihwaras, and Kedungadem sub-districts is 0,48 m3/det. The amount of discharge to rotate the turbine is 1,22 m3/det with the amount of energy generated is 59,91 MWh. With the availability of discharge in both reservoirs, both reservoirs are able to meet the needs of irrigation, raw water, and MHP for the next 10 years with the most optimum cropping pattern based on maximum profit is in alternative 2 (Paddy-Paddy-Palawija) with a total profit of Rp 601.683.497.035. In addition, the Gongseng Reservoir is able to reduce flooding by 60,87% at Q25; 60,58% at Q50; 60,41% at Q100; 58,64% at Q1000 and 45,94% at QPMF.